METASTATIC CUTANEUS MELANOMA OF THE GALLBLADDER-CASE REPORT - Prgova Veljanova, Biljana; Nancheva Bogoevska, Andrea; Bozinovska Beaka, Gordana; Gjoreski, Aleksandar; Nancheva, Jasminka (Association of medical doctors "Sanamed" Novi Pazar, 2019)
Melanoma is an aggressive malignant tumor that originates from melanocytes and most com- monly occurs on the skin. Dominantly metastasize to regional lymph nodes, in the brain and lungs and rarely in the gastrointestinal (GI) system. The aim of this re- port is to present a rare case of metastasis of cutaneous malignant melanoma in the gallbladder, discovered 10 months after excision of the primary melanoma of the skin. A 45-year-old patient was hospitalized in our hos- pital due to abdominal pain in right upper quadrant and nausea lasting for 7 days. An intraluminal substrate was found in the gallbladder with computed tomogra- phy and later a CT guied biopsy was performed on it, thus proving a metastatic deposit of primary malignant melanoma. Metastatic deposits in the gallbladder are extre- mely rare finding, and 238 cases have been described in the literature.
Keywords: malignant melanoma; mestastases; CT; biopsy; gallbladder